The Impact of Macroeconomic Variables Shocks on Sustainable and Islamic Indices in Indonesia (2016-2023) - Wijayanti, Fitri; Pramono, Sigid Eko; Indra, Indra (Universitas Pendidikan Indonesia, 2024)
Purpose – This study aims to analyze the influence of shocks in macroeconomic variables on the Sharia index and sustainable index represented by ISSI and JII as the Sharia index and SKEHATI as the sustainable index on the Indonesia Stock Exchange. By studying the impact of macroeconomic shocks on the aforementioned indices, it is hoped to provide guidance for investors and stakeholders in making investment decisions and taking appropriate precautions in fluctuating market conditions.Methodology – Descriptive quantitative analysis with VAR/VECM analysis to examine the shocks of macroeconomic factors to the three indices. The data used consists of the data from the last 10 years from Bloomberg’s terminal.Findings – From this study, it was found that JII can respond to macroeconomic shocks more quickly compared to ISSI and SKEHATI. SKEHATI is the dominant factor influencing the Sharia index, including ISSI and JII.Keywords: impact, Islamic index, macroeconomic shocks, sustainable index, VAR/VECM